Severe mitral valve papillary muscle rupture of isolated Whipple's endocarditis: a case report and review of the literature - Shi, Yan; Wang, Xinchen; Mao, Xinxin; Mi, Liangyu; Liu, Wanglin; Wang, Na (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTropheryma whipplei endocarditis (TWE) is rarely reported. Diagnosis is particularly challenging when it occurs as isolated TWE without classical manifestations of Whipple's disease.Case presentationA 35-year-old Asian female with systemic lupus erythematosus presented with acute heart failure secondary to mitral valve papillary muscle rupture as her sole symptom, requiring emergent veno-arterial extracorporeal membrane oxygenation support and urgent valve replacement. Intraoperative absence of vegetations and negative conventional microbiological examination preliminarily ruled out infective endocarditis. However, on postoperative day (POD) 3, her condition rapidly deteriorated into septic shock. Follow-up chest CT revealed bilateral asymmetric pulmonary infiltrates inconsistent with cardiogenic pulmonary edema alone. Metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid detected T. whipplei, providing a crucial diagnostic breakthrough. Subsequent periodic acid-Schiff staining of the resected valve confirmed the definitive diagnosis of isolated TWE. Targeted meropenem therapy for 5 days resulted in significant improvement in both pneumonia and septic shock, permitting ECMO discontinuation. The patient was successfully extubated by POD 12 and discharged on POD 22 with oral co-trimoxazole and doxycycline in a stable condition.ConclusionWe present the first case of isolated TWE in a young Asian female, notable for its atypical clinical presentation, fulminant progression, and profound diagnostic challenges. Clinicians should maintain a high vigilance for blood culture–negative endocarditis. Timely diagnosis and appropriate treatment are crucial for improving prognosis. mNGS analysis of samples from suspected disseminated sites may yield crucial diagnostic breakthrough.